2021
DOI: 10.1111/febs.15711
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing heptadecaphobia: TH17 cells and associated cytokines in cancer and metastasis

Abstract: Cancer is one of the leading causes of death worldwide. When cancer patients are diagnosed with metastasis, meaning that the primary tumor has spread to at least one different site, their life expectancy decreases dramatically. In the past decade, the immune system´s role in fighting cancer and metastasis has been studied extensively. Importantly, immune cells and inflammatory reactions generate potent antitumor responses but also contribute to tumor development. However, the molecular and cellular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 256 publications
(586 reference statements)
0
6
0
Order By: Relevance
“…It remains possible that each Fscn1 inhibitor may evoke distinct off-target effects, as evidenced by the inhibitory versus stimulatory effect of NP-G2-044 and BDP-13176 on F-actin levels, respectively, as well as the coactivating potential of NP-G2-044 in CD8 + T cells. Furthermore, we also noted that treatment of DC/T-cell cocultures with BDP-13176 but not NP-G2-044 at low to intermediate concentrations favored production Th2- (IL-13) and Th9- (IL-9) [ 46 ] associated cytokines, whereas NP-G2-044 at the lowest concentration upregulated Th17-associated IL-17 [ 47 ] production.…”
Section: Discussionmentioning
confidence: 89%
“…It remains possible that each Fscn1 inhibitor may evoke distinct off-target effects, as evidenced by the inhibitory versus stimulatory effect of NP-G2-044 and BDP-13176 on F-actin levels, respectively, as well as the coactivating potential of NP-G2-044 in CD8 + T cells. Furthermore, we also noted that treatment of DC/T-cell cocultures with BDP-13176 but not NP-G2-044 at low to intermediate concentrations favored production Th2- (IL-13) and Th9- (IL-9) [ 46 ] associated cytokines, whereas NP-G2-044 at the lowest concentration upregulated Th17-associated IL-17 [ 47 ] production.…”
Section: Discussionmentioning
confidence: 89%
“…Notably, several immune cells can produce IL-22, for example, Th22, Th17, ILC3, and NKT cells. 19 , 34 , 35 We previously showed that NKT cells and T cells are the key sources during the early step of metastasis, namely extravasation, in liver and lung metastasis, respectively. 19 Interestingly, in established lung metastasis, Th22 cells were identified as the key source of IL-22 in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells have a controversial role in different cancers. They mediate antitumor effects by recruiting immune cells into tumors or stimulating effector CD8 + T cells (26) as well as tumor-promoting responses driving proliferation, invasion, metastasis, and angiogenesis (27,28). Although the presence of Th17 cells in situ was linked with cervical cancer progression (6,10), and IL-17A was found to upregulate MMP-2 and MMP-9 expression favoring migration of cervical cancer cell lines (27), Th17-induced mechanisms underlying cervical cancer metastases are not reported so far.…”
Section: Discussionmentioning
confidence: 99%